Evaluate the method of arrange math Teacher at college of education according to analysis system (Journal of the College of Basic Education, 2019)
The present research aims to evaluate method of arrange math teacher at college of education according to analysis system The sample of the study includes(15) teachers and (162) male and female students from the first and fourth degree in math. dept. in Mustansiriyah university /college of education for the academic year (2018-2019) .To achieve the aim, the researcher choose the methods arrangement to analysis system at college of education limit the element of system stage to: input – process- output, and analysis System element which include (16) analysis to many symbol include (64) and Put activity normative level for every element, and to identify tools for measuring system elements, the researcher has adopted a questionnaire about teachers opinion contain (40) item which present the system content at three stages , and acknowledge test contain (30) different items, and the measurement for measure the habit study which contain (57) items ,and attitudes measurement contain (50) item, and information collection forms for the university building, number of teaching staff and titles, number of books and researches, number of students and average scores, number of students leaving, two observation forms are also used one to observe the teachers which contain (9) items, and one for practice teacher which contain (15) items, the results of the research have proved The system and its indicators as a whole agree very well as expected in the system of preparation and completion rate (0.72) , In the light of the results, the researcher has concluded some conclusion and also has suggested and recommended many items